Exploitation of the brain-gut axis: Role of Plantago albicans polysaccharides in aluminium-induced neurotoxicity - BEN KADDOUR Khaoula; LEGSEIR Amira; MOUFFOK Insaf; ZEKKOUR Fatma (. جامعة الوادي.Université d'EL-Oued., 2025)
This study aims to investigate the gut-brain axis using polysaccharides of Plantago albicans, and to evaluate its effect on the gut microbiome and neurobehavioral responses in aluminum chloride induced Alzheimer’s disease in animal model. Chemical analysis using colorimetric assays revealed that the extracted fraction, named PAP, has concentrations of 72.92% in total sugars, 64.53%, in neutral sugars, approximately 5% in protein, and a very low polyphenol content of 1.21%. FTIR results showed characteristic peaks indicating the presence of functional groups related to polysaccharides, such as out-of-plane vibrations of C–H and O–H at 600 and 650 cm⁻¹. In vivo experimentation was conducted on four groups of six Wistar rats. The study groups were named N, T, C-, and C+ indicating the individuals that received standard diet, PAP, AlCl₃, and PAP with AlCl₃, respectively. In vivo biological assessments on W. albino rats exposed to aluminum chloride indicated that Plantago albicans polysaccharides extract (PAP) partially improved oxidative balance in the brain, as evidenced by non-significant reduced MDA levels and a increase in GSH; p > 0.05. Conversely, a significant decrease in GSH was observed in some healthy rats following PAP administration (p ≤ 0.05), suggesting a possible pro-oxidant effect in T group. The results showed that polysaccharides from Plantago albicans possesses antioxidant and antiinflammatory properties, which positively influenced the rat's neurobehavioral performance and contributed to restoring gut microbiome balance. Moreover, colon sections indicated a reduction in submucosal thickness in C- group and an increase in mucosal thickness in C+ and T groups, indicating the positive effect of PAP on gut health. Additionally, the intestinal health index was positively correlated with higher antioxidant levels (GSH) in the kidneys and heart (p ≤ 0.05), reflecting the relationship between the gut health and the oxidative stat of the individual. Microscopic examinations showed that the aluminum chloride group (C⁻) suffered from thickening of blood vessel walls, surrounding hemorrhages, neuronal cell death, abnormal cell morphology, as well as infiltration of astrocytes and lymphocytes. In contrast, the C+ group exhibited a normal cerebral cortex and slight capillary proliferation, indicating the protective and therapeutic effect of PAP against aluminum-induced brain damage.
Applied Biochemistry
Keywords: Plantago albicans; polysaccharides; gut-brain axis; Alzheimer's disease; aluminum chloride.